2008
DOI: 10.1055/s-2008-1062746
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2: Development, Analytical Characterization, and Clinical Testing of a New ELISA

Abstract: Lipocalin-2 (also known as neutrophil gelatinase-associated lipocalin [NGAL]) has been described as a promising marker of metabolic syndrome associated with inflammation. The aim of our work was to develop an assay for the determination of lipocalin-2 in human serum and to investigate its levels in healthy volunteers and donors suffering from metabolic syndrome. We also conducted a pilot study on individuals with metabolic syndrome and on healthy probands and measured lipocalin-2 in these individuals. We devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 5 publications
8
49
4
1
Order By: Relevance
“…There are several basic residue-rich regions in ANGPTL 3 and 4, both in N-and C-terminal regions that could mediate the binding of these proteins at the sites important for LPL activity. For ANGPTL3, good agreement with previous reports showing that ANGPTL3 is present in the circulation at a higher concentration (224 ng/ml) compared with ANGPTL4 (1.73 ng/ ml) ( 22,23 ). Although some differences exist in the values reported for ANGPTL 3 and 4, these probably are due to differences in method standardization, population samples, and/or the antibodies used.…”
Section: Effect Of Heparin On Human Angptl 3 and 4 In Vivo And In Vitrosupporting
confidence: 76%
“…There are several basic residue-rich regions in ANGPTL 3 and 4, both in N-and C-terminal regions that could mediate the binding of these proteins at the sites important for LPL activity. For ANGPTL3, good agreement with previous reports showing that ANGPTL3 is present in the circulation at a higher concentration (224 ng/ml) compared with ANGPTL4 (1.73 ng/ ml) ( 22,23 ). Although some differences exist in the values reported for ANGPTL 3 and 4, these probably are due to differences in method standardization, population samples, and/or the antibodies used.…”
Section: Effect Of Heparin On Human Angptl 3 and 4 In Vivo And In Vitrosupporting
confidence: 76%
“…A previous study in adults showed higher concentrations of plasmatic lipocalin-2 in obese subjects (10), but these results have not been corroborated by other authors (27). It is noteworthy that, despite obtaining clear differences between obese and lean children in our studied cohorts, lipocalin-2 levels were not related to BMI and waist circumference.…”
Section: Without Weight Losscontrasting
confidence: 42%
“…However, Jun et al, (2011) found no effect of global ablation of lipocalin-2 on obesity-mediated insulin resistance in vivo. In obese humans no statistically significant effect of BMI was found on circulating levels of lipocalin-2 (Stejskal et al, 2008) and this was confirmed by . Furthermore lipocalin-2 was found in and released almost exclusively by the nonfat cells rather than the fat cells isolated from human omental adipose tissue .…”
Section: Lipocalin-2supporting
confidence: 62%